2013 43rd Annual IEEE/IFIP International Conference on Dependable Systems and Networks (DSN) 2013
DOI: 10.1109/dsn.2013.6575364
|View full text |Cite
|
Sign up to set email alerts
|

Crossing the threshold: Detecting network malfeasance via sequential hypothesis testing

Abstract: The domain name system plays a vital role in the dependability and security of modern network. Unfortunately, it has also been widely misused for nefarious activities. Recently, attackers have turned their attention to the use of algorithmically generated domain names (AGDs) in an effort to circumvent network defenses. However, because such domain names are increasingly being used in benign applications, this transition has significant implications for techniques that classify AGDs based solely on the format o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 17 publications
0
14
0
Order By: Relevance
“…Antonakakis et al [16] proposed Pleiades, which clusters non-existent domains based on character distributions within the domain names and on the querying hosts, using the strategy on DNS traffic from large ISPs to discover six DGAs that were unknown at that time. Krishnan et al [53] detected hosts in a botnet by analyzing patterns in DNS queries for non-existent AGDs through sequential hypothesis testing. Mowbray et al [64] detected hosts that query domains with an unusual length distribution, deriving 19 DGAs of which nine were previously unknown.…”
Section: Related Workmentioning
confidence: 99%
“…Antonakakis et al [16] proposed Pleiades, which clusters non-existent domains based on character distributions within the domain names and on the querying hosts, using the strategy on DNS traffic from large ISPs to discover six DGAs that were unknown at that time. Krishnan et al [53] detected hosts in a botnet by analyzing patterns in DNS queries for non-existent AGDs through sequential hypothesis testing. Mowbray et al [64] detected hosts that query domains with an unusual length distribution, deriving 19 DGAs of which nine were previously unknown.…”
Section: Related Workmentioning
confidence: 99%
“…Since DGAs o en generate hundreds of domains per day and at most only a few of those domains are actually registered by the a acker, large numbers of these requests result in NXDomains. Many NX-Domain responses from the same computer are unlikely to result from expected user behaviour, and thus this pa ern of DNS tra c can be associated with DGA activity [8,22,52].…”
Section: Domain Generation Algorithms (Dgas)mentioning
confidence: 99%
“…Future techniques included more contextual information which improved the longevity of detection systems. Clustering [51,52,59], Hidden Markov Models (HMMs) [8], random forests models [40,47,53], and sequential hypothesis testing [22] used data such as WHOIS or NXDomain responses with the domain to identify DGAs. However, a number of these techniques require batches of live data to maintain relevancy or high volumes of data which are not typically feasible in real-time environments.…”
Section: Related Workmentioning
confidence: 99%
“…Using a multi-month evaluation phase, they showed that the system could achieve very high detection accuracy. In 2013, Krishnan et al [12] proposed a method for detecting attack activity using Sequential Hypothesis Testing. They believed that hosts that have been infected by malware will exhibit a domain name scanning behavior.…”
Section: Related Workmentioning
confidence: 99%